Tubercular Stricture at Lower End of Ureter Causing Vesicoureteric Junction Obstruction: Our Experience in Rangpur Medical College (Bangladesh Journal of Urology, 2020)
Objective: To determine the outcome of ureteroneocystostomy for vesicoureteric junction obstruction due to tubercular stricture.Patients and Method: Twelve patients age from 19 years to 47 years were underwant uretroneocystostomy with ifilateral D-J stanting for vecicoureteric junction obstruction (VUJO) with proximal hydroureteronephrosis tissue from the lower of the ureter shows granunation lesion complatable with tuberculosis. D-J stant were remove and patients were put into antitubercular chemotherapyResults: Patients were symptom free and follow up IVU at six months interval shows free passage of contrast at 10 minutes film.Conclusion: Vesicoureteric junction obstruction (VUJO) due to lower ureteric stricture by tuberculus lesion, though rare, should be searched, because if not treated properly may lead to damage of ipsilateral renal unit.Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.13-17